Development of a novel liquid crystal based 3D micro-tissues culture technique and microfluidic vibrational cleaner - Thong, Kok Tung (2016)
The conventional 2D culture technique used for producing monolayer of cells in the petri dish was widely practiced in the life sciences laboratory. However, this culture technique produced the organisation of cells that were far from the natural tissue and the outcomes for biological studies were not reliable. In this research, liquid crystal was exploited as a new culture technique to produce 3D micro-tissues of human keratinocyte cell lines (HaCaT). The development of 3D micro-tissues technique initiated with the optimisation of different cell density on the coated cholesteryl ester liquid crystal (CELC) substrate to obtain a higher number and larger sized of micro-tissues. The investigation of 3D micro-tissues physical characteristic included the analyses of cell-to-cell interaction, cell organisation, biochemistry element in micro-tissues, cell response to enzymatic dissociation treatment, immunostaining and cell viability study of micro-tissues. A microfluidic vibrational cleaner constituted polydimethylsiloxane (PDMS) microfluidic chip and electronic system were developed to remove the residue liquid crystal from the extracted micro-tissues. Based on the cell monitoring and immunostaining, HaCat cells were found with the ability to self-aggregate with adjacent cells and organised into microspheroid on liquid crystal substrate. This culture technique was able to maintain the cell viability of the micro-tissues around 80%. In addition, the micro-tissues presented potential to be re-cultured on polystyrene culture dish again. The liquid crystal residue on the extracted micro-tissues was effectively cleaned by the vibrational cleaner at a frequency of 148 Hz and acceleration of 0.89 Grms. The liquid crystal based 3D micro-tissue culture technique and the cleaning device was reliable to produce cleaned micro-tissues.